1983
DOI: 10.1111/j.1528-1157.1983.tb03420.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of the Sleep EEG With and Without Sleep Deprivation in Patients With Atypical Absences

Abstract: Hitherto it has not been known whether or not the sleep EEG after sleep deprivation is more effective than the simple or drug-induced sleep EEG. To investigate this, we recorded for 32 patients both sleep EEGs without sleep deprivation and, on the following day, sleep EEGs after 24 h of sleep deprivation. All the patients had atypical absences which were almost exclusively combined with generalized seizures or some other seizure types. All patients were receiving antiepileptic therapy. Sleep without sleep depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…There is an activating effect from SD on IEDs aside from the sampling effect or the activating effects of sleep. IEDs may occur with greater frequency during wakefulness after SD in the interval before sleep than in wakefulness without SD (Degen and Degen, 1981;Degen and Degen, 1983;Degen and Degen, 1991;Degen et al, 1987). However, the activating effect of SD was greatest during sleep in most but not all studies (Mendez and Radtke, 2001).…”
Section: Sleep and Sdmentioning
confidence: 94%
“…There is an activating effect from SD on IEDs aside from the sampling effect or the activating effects of sleep. IEDs may occur with greater frequency during wakefulness after SD in the interval before sleep than in wakefulness without SD (Degen and Degen, 1981;Degen and Degen, 1983;Degen and Degen, 1991;Degen et al, 1987). However, the activating effect of SD was greatest during sleep in most but not all studies (Mendez and Radtke, 2001).…”
Section: Sleep and Sdmentioning
confidence: 94%
“…Many studies suggest a specific activating effect of SD per se, pointing out that EEG activation is already present during the waking phases of the EEG recorded after SD (Degen, 1980;Degen and Degen, 1983;Degen et al, 1987;DeRoos et al, 2009;Mattson et al, 1965;Pratt et al, 1968;Schwarz and Zangemeister, 1978;So et al, 1994;Tartara et al, 1980). Fountain et al (1998) specifically addressed this aspect and showed significant IED incidence both during wakefulness and sleep SD EEG epochs, inferring that the EEG activation was exclusively due to SD, rather than to the occurrence of sleep.…”
Section: Specific Effect Of Sd or Simple Effect Of Drowsiness/sleep?mentioning
confidence: 95%
“…Recent seizures occurrence Degen (1980), Degen and Degen (1983), Gandelman-Marton and Theitler (2011), Pratt et al (1968) Earlier or recent seizure onset Degen (1980), Degen andDegen (1991, 1983), Degen et al (1987) Previous history of repeated seizures DeRoos et al (2009), Gandelman-Marton and Theitler (2011) Higher seizure frequency Degen and Degen (1983) Delayed psychomotor development Degen (1980), Degen and Degen (1983), Degen et al (1987) Coexistent neuropathological conditions Degen (1980), Degen and Degen (1983), Degen et al (1987) Personality changes Degen and Degen (1983) Family history of epilepsy Degen et al (1987) Female gender Degen andDegen (1991, 1981), Degen et al (1987) Children and young patients Degen (1980), Degen and Degen (1991), Degen et al (1987), Roth et al (1986), DeRoos et al (2009 in the 1960s performed an additional basal EEG in those patients in whom SD EEG had shown IEDs. The proportion of SD-positive patients showing IEDs in a second basal EEG ranged from 18.8% (Mattson et al, 1965) to 12.8% (Pratt et al, 1968) and to a striking 0% in Geller et al (1969).…”
Section: Factors Referencementioning
confidence: 99%
“…Several studies have suggested that TSD can be useful in activating IEDs in wakefulness, especially in patients with IGE (Degen et al, 1980;Degen et al, 1981;Degen et al, 1983;Degen et al, 1987;El-Ad et al, 1994;Fountain et al, 1998;Geller et al, 1969;Klinger et al, 1991;Pratt et al, 1968;Ropakiotis et al, 2000;Roth et al, 1986;Scollo Lavizzari et al, 1977;Tartura et al, 1980;Veldhuizen et al, 1983). Fountain et al (1998) found that 7% of subjects had IEDs during wakefulness only after TSD.…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 96%
“…In a series of studies in the 1980s, Degen and colleagues compared the effects of TSD on EEGs of subjects with different seizure types and epilepsy syndromes (Degen et al, 1981;Degen et al, 1983;Degen et al, 1987). For most seizure types, they found that spontaneous sleep and sleepdeprived recordings produced similar activation rates (awakening grand mal, 77% versus 71%; atypical absence, 78% versus 72%; absence epilepsy, 69% versus 71%; CPS, 49% versus 51%).…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 98%